Implementation of a Digital Accounting System to Increase the Efficiency of Financial Reports in MSMEs in Gowa Regency, Indonesia - Ujianti Tawakkal; S. Sudirman; S. Supiati (Golden Ratio of Auditing Research, 2026)
This research aims to determine the implementation of digital accounting systems on the increase of financial report efficiency in Small and Medium Enterprises (SMEs) in Gowa Regency. The study employs a quantitative method using simple regression analysis to investigate how the application of digital accounting systems impacts the efficiency of financial reports among Micro, Small, and Medium Enterprises (SMEs) in Gowa Regency. Data were collected from 45 SME respondents using instruments that had been tested and proven to be valid and reliable. The results of the regression analysis show a positive and significant relationship between the increase in financial report efficiency and the implementation of digital accounting systems. A correlation coefficient (R) value of 0.661 indicates a strong relationship, and the coefficient of determination (R2) of 0.436 suggests that the increase in financial report efficiency accounts for 43.6% of the variation in the implementation of digital accounting systems. Other factors influence the remaining variation. The model's feasibility was validated by the ANOVA test (F=33.306; Sig. =0.000). According to the regression coefficient (B=0.523), a one-unit increase in financial report efficiency will result in a 0.523-unit increase in the implementation of the digital accounting system. The findings indicate that SMEs' perception of efficiency benefits, such as ease of decision-making, accuracy, and data speed, is the primary factor driving the adoption of digital accounting systems. However, successful implementation relies heavily on four factors: the ability to use the application, understanding of financial reports, ease of system access, and technological support.